Estimation of cauliflower mass transfer parameters during convective drying - Sahin, Medine; Doymaz, Ibrahim (SPRINGER, 2017)
The study was conducted to evaluate the effect of pre-treatments such as citric acid and hot water blanching and air temperature on drying and rehydration characteristics of cauliflower slices. Experiments were carried out at four different drying air temperatures of 50, 60, 70 and 80 A degrees C with the air velocity of 2.0 m/s. It was observed that drying and rehydration characteristics of cauliflower slices were greatly influenced by air temperature and pre-treatment. Six commonly used mathematical models were evaluated to predict the drying kinetics of cauliflower slices. The Midilli et al. model described the drying behaviour of cauliflower slices at all temperatures better than other models. The values of effective moisture diffusivities (D (eff) ) were determined using Fick's law of diffusion and were between 4.09 x 10(-9) and 1.88 x 10(-8) m(2)/s. Activation energy was estimated by an Arrhenius type equation and was 23.40, 29.09 and 26.39 kJ/mol for citric acid, blanch and control samples, respectively.
Keywords: KINETICS; PRETREATMENTS; QUALITY; HEAT; AIR; Thermodynamics; Mechanics